Effects of spaced learning in the water maze on development of dentate granule cells generated in adult mice - Trinchero, Mariela Fernanda (2015)
New dentate granule cells (GCs) are generated in the hippocampus throughout life. These adult-born neurons are required for spatial learning in the Morris water maze (MWM). In rats, spatial learning shapes the network by regulating their number and dendritic development. Here, we explored whether such modulatory effects exist in mice. New GCs were tagged using thymidine analogs or a GFP-expressing retrovirus. Animals were exposed to a reference memory protocol for 10-14 days (spaced training) at different times after newborn cells labeling. Cell proliferation, cell survival, cell death, neuronal phenotype, and dendritic and spine development were examined using immunohistochemistry. Surprisingly, spatial learning did not modify any of the parameters under scrutiny including cell number and dendritic morphology. These results suggest that although new GCs are required in mice for spatial learning in the MWM, they are, at least for the developmental intervals analyzed here, refractory to behavioral stimuli generated in the course of learning in the MWM.